PENGARUH KEPERCAYAAN DAN KUALITAS INFORMASI TERHADAP MINAT BELI ULANG PADA MARKET PLACE DI KOTA BIMA - Juwani Basrin; Intisari Haryanti (Universitas Sarjanawiyata Tamansiswa, 2020)
This study aims to determine and analyze the influence of Trust and Quality of information on repurchase interest in the Market place in the city of Bima both partially and simultaneously. The population in this study is the people of the city of Bima who have made purchases at the Market Place media. The sampling technique used was purposive sampling with 96 respondents. With multiple linear regression analysis and SPSS 22, the results show that only trust has a significant effect on the buying interest of the Bima people in the Market place while the information quality has no influence and is not significant on the repurchase intention. this is supported by the magnitude of the relationship value (R) which is 0.498 which falls on the weak relationship area.Keywords:Trust, Quality of information and Repurchase Intention